222 days without COVID in Taiwan: what are the reasons for this success? - Dai, Chia-Yen (J Travel Med, 2021)
The second wave of COVID-19 has been reported in many countries such as Vietnam after 99 days without any further local transmission since the first wave. Here we report on the success story in Taiwan in fighting the COVID-19, currently keeping 222 days without an indigenous case of COVID.